The state vs. its citizens: a note on Romania, Europe, and corruption - Barbu, Daniel (2007)
According to most accounts from home and abroad, Romania is a corrupt country. Journalists, civic activists and public prosecutors suspect every top politician, past and present, of either committing or planning to commit a felony. As far as any knowledgeable Romanian can tell, the European Commission itself is the inspiration behind the current official anti-corruption drive. Ten years ago, discussion of wider powers for prosecutors and intelligence agents would have seemed inappropriate, even indecent, reminders of the Stalinist secret police, while state prosecutions of conspicuously wealthy politicians evoke memories of communist witch-hunts against owners of private property. How could the European Commission ostensibly support Romania's use of judicial proceedings so reminiscent of the communist era? After the collapse of state socialism, western leaders were unable or unwilling to recognise that decades of communism had transformed many institutions of state. Courts, Parliam